An ius-philosophical reading of David Graeber on subject, debt, and morality - Vila-Viñas, David (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
This paper considers the relevance of David Graeber’s work, in particular Debt, for the Philosophy of Law. It analyzes his perspective on the legal phenomenon and the implications of his notions of debt and subject of interest. It focuses in particular on the effect that austerity approaches have had on them. Secondly, it attends to the axiological conflicts that emerge within our legal systems on the primacy of the obligation to pay debts and the distribution of responsibility and guilt among the subjects involved. To this end, it also considers the treatment of the question by the Spanish Constitutional Court. Finally, it introduces some possible lines of research for the transformation of Law.